2012
DOI: 10.5194/acp-12-653-2012
|View full text |Cite
|
Sign up to set email alerts
|

Combining Bayesian methods and aircraft observations to constrain the HO<sup>.</sup> + NO<sub>2</sub> reaction rate

Abstract: Abstract. Tropospheric ozone is the third strongest greenhouse gas, and has the highest uncertainty in radiative forcing of the top five greenhouse gases. Throughout the troposphere, ozone is produced by radical oxidation of nitrogen oxides (NO x = NO + NO 2 ). In the upper troposphere (8-10 km), current chemical transport models under-estimate nitrogen dioxide (NO 2 ) observations. Improvements to simulated NO x production from lightning have increased NO 2 predictions, but the predictions in the upper tropos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 29 publications
2
41
0
Order By: Relevance
“…In particular, the value for the uptake coefficient γ N 2 O 5 in GEOS-Chem is high compared to recent laboratory and field estimates of this value (e.g. Brown et al, 2009;Mollner et al, 2010;Henderson et al, 2012;Butkovskaya et al, 2007Butkovskaya et al, , 2009. We conclude that the nested GEOS-Chem CTM is in close agreement with OMIobserved NO 2 columns over Europe.…”
Section: Evaluation Of Geos-chem and Omi Tropospheric No 2 Columnssupporting
confidence: 66%
“…In particular, the value for the uptake coefficient γ N 2 O 5 in GEOS-Chem is high compared to recent laboratory and field estimates of this value (e.g. Brown et al, 2009;Mollner et al, 2010;Henderson et al, 2012;Butkovskaya et al, 2007Butkovskaya et al, , 2009. We conclude that the nested GEOS-Chem CTM is in close agreement with OMIobserved NO 2 columns over Europe.…”
Section: Evaluation Of Geos-chem and Omi Tropospheric No 2 Columnssupporting
confidence: 66%
“…GEOS‐Chem uses the rate constant recommended by the NASA Jet Propulsion Laboratory panel evaluation (Sander et al, ). Several studies have suggested that this rate constant might be 15–20% lower than the value recommended by Jet Propulsion Laboratory (Henderson et al, ; Mollner et al, ). As no measurements of OH, HO 2 , or H 2 O 2 were made as part of WINTER, we cannot directly evaluate our modeled OH concentrationss.…”
Section: Resultsmentioning
confidence: 99%
“…The NO x /NO y ratio described in this work was corrected for this contribution. For the calculation, we conservatively assumed the average OH concentration of 2.0 × 10 6 molecules cm −3 and the rate constant for the reaction of NO 2 + OH → HNO 3 to be k = 2.58 × 10 −11 [ Henderson et al ., ], used in recent estimates of NO x lifetime in continental regions [ Browne and Cohen , ].…”
Section: Methodsmentioning
confidence: 99%